Biological variations, technical stability and elution tactics in dried blood spots specimens: neonatal screening outcomes - Subhasree C.R.; Samu Subramaniam; Shyama Subramaniam (Pediatric Review: International Journal of Pediatric Research, 2019)
For many years, pre-analytical variables were only inappropriately considered in the field of dried blood spots (DBS) testing and even today, with the exception of newborn screening, the entire pre-analytical phase, which comprises the preparation and processing of DBS for their final analysis has not been standardized. (1) compared to conventional venepuncture, less blood volume is required and this fact was most important in paediatric diagnostics; (2) blood collection is simple, non-invasive, and inexpensive; (3) the risk of bacterial contamination or haemolysis is minimal; and (4) DBS can be preserved for long periods with almost no deterioration of the analytes. Advances techniques applied to diagnose the disorders of Inborn errors of metabolism. Dried blood spots (DBSs) have potential use in remote health applications for individual and population diagnosis, and can enable epidemiological surveillance for known and unknown diseases. DBS sampling offers great potential for remote health applications as a cost-effective sample format for large-scale screening and diagnostic purposes, but the DBS samples often need to be transported from remote sampling locations (e.g., tropical or developing countries) to analytical laboratories where the quantitative measurements of different metabolic or disease biomarkers can be carried out. Dried blood spots are commonly method for collecting, storing, transporting, and analysing a variety of human body fluids. Since 2006, however a variety of new and innovative dried blood spots applications, although this pre-analytical approach represents an interesting alternative to classical venous blood sampling, its routine use is limited. Here, we review the application of DBS technology in clinical chemistry, molecular assays, small molecules, and large molecules all are perfectly suited to evaluate its future role supported by new analytical methods such as mass spectrometry.